Comparative Studies of National Incomes and Prices - Kravis, Irving B. (Journal of Economic Literature, 1984)
Income comparisons between persons or groups of persons in different countries are a special field of inquiry because there are different currency units. For the most part, the other theoretical and empirical problems encountered in international income comparisons are similar to those of within-nation comparisons between different persons at the same time or different groups of persons either interspatially or, what is more common, intertemporally (e.g., constant price series of national income). The qualifications mainly and the most part are included because some writers hold that international comparisons are complicated or even invalidated by differences in consumption patterns. Sometimes differences in tastes are held to underlie these variations in consumption patterns, variations that are often much larger between countries than those found between regions within a country or between different periods in the same country. This essay focuses, in its methodological aspects, on these special problems. The basic problems that are common to international and within-nation comparisons are left to the standard literature on national accounts.2 We turn now to the currency unit problems and reserve the question of tastes for a later section.